Flexible Gas Sensor Based on PANI/WO3/CuO for Room-Temperature Detection of H2S - Dongxiang Zhang; Yingmin Liu; Yang Wang; Zhi Li; Dongkun Xiao; Tianhong Zhou; Mojie Sun (Sensors)
Polyaniline (PANI) is currently one of the most extensively studied conductive polymers in the field of flexible gas sensors. However, sensors based on pure PANI generally suffer from problems such as low sensitivity and poor stability. To address these issues, in this work, a room-temperature hydrogen sulfide gas sensor of polyaniline/tungsten oxide/copper oxide (PANI/WO3/CuO) was synthesized using in situ polymerization technology. This gas sensor displays a response value of 31.3% to 1 ppm hydrogen sulfide at room temperature, with a response/recovery time of 353/4958 s and a detection limit of 100 ppb. Such an excellent performance is attributed to the high surface area and large adsorption capacity of the ternary composite, as well as the multi-phase interface synergistic effect.